The moderating effect of perceived social support on stress and depression among university students - Talwar, Prashanth (Online Journal of Health and Allied Sciences, 2016)
Background and objectives : The omnipresence of stress and depression among university students is a cause for concern, as it can have adverse consequences on all aspects of their life. Understanding the role of social support as a protective factor within this context, may well be vital to the enhancement of overall wellbeing among students. The main aim of the present study was to examine the moderating effect of perceived social support on the relationship between stress and depression. Methods: A cross-sectional survey was conducted to garner data from 254 university students for hierarchical multiple regression and structural equation modeling analysis. Results: Firstly, the present study replicated the frequently reported positive relationship between stress and depression. Secondly, an inverse association between social support and depression was also depicted. Finally, the results also supported an interaction between perceived social support and stress in predicting depression among students. Conclusion: In sum, the results of the current study may well augment our understanding of the role of perceived social support in combating stress and depression among students, and thereby convey important implications for intervention strategies tailored to this demographic